DNA Methylation: A Target in Neuropathic Pain - Jiang, Wei; Tan, Xuan-Yu; Li, Jia-Ming; Yu, Peng; Dong, Ming (Frontiers in Medicine, 2022)
Neuropathic pain (NP), caused by an injury or a disease affecting the somatosensory nervous system of the central and peripheral nervous systems, has become a global health concern. Recent studies have demonstrated that epigenetic mechanisms are among those that underlie NP; thus, elucidating the molecular mechanism of DNA methylation is crucial to discovering new therapeutic methods for NP. In this review, we first briefly discuss DNA methylation, demethylation, and the associated key enzymes, such as methylases and demethylases. We then discuss the relationship between NP and DNA methylation, focusing on DNA methyltransferases including methyl-CpG-binding domain (MBD) family proteins and ten-eleven translocation (TET) enzymes. Based on experimental results of neuralgia in animal models, the mechanism of DNA methylation-related neuralgia is summarized, and useful targets for early drug intervention in NP are discussed.